Supercritical CO2 extraction of oil from Moroccan unroasted Argan Kernels: Effects of process parameters to produce cosmetic oil. (May 2022) - Mouahid, Adil; Claeys-Bruno, Magalie; Bombarda, Isabelle; Amat, Sandrine; Ciavarella, Andrea; Myotte, Emmanuelle; Nisteron, Jean-Paul; Crampon, Christelle; Badens, Elisabeth
Abstract: The effects of process parameters: pressure (200 – 400 bar), temperature (313 – 333 K), and flow rate (0.11 – 0.27 kg/h) on the efficiency of extraction process of Argan oil by supercritical CO2 were investigated using response surface methodology and mathematical modelling (Sovová's mathematical model). The fastest extraction kinetics corresponding to the optimal operating conditions were obtained at 400 bar, 333 K at a CO2 flow rate of 0.11 kg corresponding to a residence time of about 8.8 min. A tocopherol rich oil can be obtained at the beginning of the extraction experiment. Graphical Abstract: ga1 Highlights: The optimal operating conditions for the extraction of argan oil using supercritical CO2 were reported. The effects of pressure, temperature and flow rate on oil solubility and extraction efficiency were investigated. The effects of SC-CO2 time residence in the extraction on the extraction kinetic of argan oil were investigated. Sovova's BIC mathematical model was applied for a better understanding of the mechanism of extraction kinetics. The effect of pressure on the oil composition (fraction of fatty acid) was determined.